Retention of residual formaldehyde in treated Indian mackerel (Rastrelliger kanagurta) under iced storage and related food safety concern - Jawahar, Laly S.; John, Christy; Shafeekh, Muhammed; Anupama, T. K.; Sankar, T. V. (Indian Journal of Fisheries, 2018)
Indian mackerel Rastrelliger kanagurta dip-treated with different concentrations of formaldehyde (0.2, 0.5 and 1%) was stored in ice along with untreated control fishes and evaluated the formaldehyde residue level as well as changes in pH, total volatile base nitrogen (TVBN), aerobic plate count (APC) and sensory quality, during the 24 days storage period. Formaldehyde residue levels of 7.61±0.5, 13.83 ±2.21 and 20.7±2.02 mg kg-1 were recorded in 0.2, 0.5 and 1% treatments. Initial decrease in APC and its slow increase during storage was noticed. Shelf life of 18 days for 0.2 and 0.5% formalin treated fishes and 22 days for 1% treated fishes as compared to just 10 days in control fishes was observed. Marketed fishes with fresh appearance having higher values of TVBN, lower microbial load and with a higher formaldehyde residue can be considered as clear indications of formaldehyde treatment. Since fresh appearance of treated fishes can mislead the consumers, monitoring of formaldehyde residue, microbial and biochemical indices of ice stored fishes coming in markets needs to be undertaken in order to control marketing of fishes treated with the harmful chemical.